Predstavitev pametne žoge SportIQ za spremljanje in vrednotenje meta na koš - Marković, Marko (Šport (Ljubljana), 2021)
The use of the SportIQ basketball and the pertaining application enables a simple and fast generation of some of the most important kinematic parameters of a shot at the basket. Basketball shots are the most important and the most demanding skill in the game of basketball that do not receive enough attention in the training process. The trends in modern elite basketball are moving towards increasingly better physical (motor) abilities of basketball players and increasing precision in shooting at the basket. Given the development of such modern technologies, as the SIQ basketball is, their introduction in the training process is only a matter of time. The main advantage of this technology is that the data are obtained in real time, therefore players can consider (i.e. use) the feedback about their shot immediately, i.e. in the very next shot. Thus, they can influence the technical implementation of the shot effectively. At the same time, the technology enables detailed statistical data on the shooting performance, which can be a useful support and basis for coaches when planning the training process and timing the so-called shooting form.
Keywords: basketball; diagnostics; diagnostika; IKT; košarka; met na koš; shot at the basket; sodobna tehnologija; sport; šport; technology